A Borrowed Place on Borrowed Time: Childhood, Ambivalence and the Symbolic Power of the Japanese Occupation of Hong Kong in Martin Booth’s Music on the Bamboo Radio (1997) - Paiva, Ana Brígida (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
Martin Booth‟s Music on the Bamboo Radio, published in 1997 (the year of Hong Kong‟s transfer of political sovereignty to China), is a young adult novel set during the Japanese occupation of Hong Kong. The 1941-1945 Japanese occupation represents a turning point in Sino-British relations, symbolising the beginning of the end of British rule in East Asia: although Britain regained administrative powers over Hong Kong at the end of World War II, the island of Hong Kong, Kowloon peninsula and the New Territories (according to treaties signed in 1898, following China‟s defeat in the Opium Wars) were inevitably to be returned to China at the end of the 20th century. By juxtaposing these two eras, Martin Booth explores the anxieties of a falling empire, and the uncertainty towards the future of post-handover Hong Kong, through the perspective of Nicholas, a British child raised in a territory under temporary and precarious colonial rule. This article examines how the author, by setting the novel during the Japanese occupation of Hong Kong, subverts colonial power structures, placing both British and Hong Kong Chinese as oppressed allies against a common enemy; and explores how post-handover anxieties are expressed through the ambivalent alignment of symbols of Japanese and British oppression, the use of metaphors of decrepitude, and representations of overt and covert forms of resistance to colonial occupation.